Full-semester and time-compressed fluency disorders course: an evaluation of student perceptions of competence, satisfaction, and workload - Shari L. DeVeney; Amy F. Teten; Mary J. Friehe (Social Welfare: Interdisciplinary Approach)
This article addresses the effectiveness of a time-compressed four-week course format compared to a full-semester 16-week format for a graduate-level course.  Participants were 78 students enrolled in a speech-language pathology course, fluency disorders. No significant differences were noted for student competency self-perceptions.  However, time-compressed students reported significantly higher levels of course satisfaction and workload difficulty.